PENILAIAN EFISIENSI RELATIF PAKET INTERNET HOTROD 3G+ BAGI PELANGGAN XL - Hardiyan Hardiyan (LPPM Universitas Bina Sarana Informatika, 2013)
The Internet is a very important need for people who have busy, both employers, workers andStudents. See developments, XL provides a diverse selection of Internet packages to customers,one of which is XL HotRod 3G+ Packages. It offered at affordable prices to its customers with thebonus quota and high speeds access. Surfing on the Internet use XL’s fastest 3G network andstable (XL, 2013). The purpose of this paper to assess whether any type of internet package XLHotRod 3G+ is efficient for its customers related to the price offered by the total quota, the activeperiod and speed of access. Researchers assess the relative efficiency assessment package withData Envelopment Analysis (DEA) method. The result obstained, ie there are 3 (three) typesinternet package that have not been efficient from 6 (six) package in XL HotRod 3G+.Keywords: Efficiency, Internet Packages, Data Envelopment Analysis (DEA)